TAMAN BUNGA NUSANTARA FOUNDATION'S PROMOTIONAL STRATEGY TO INFLUENCE CONSUMERS - Pupu Jamilah; Destiana Husnul Chotimah; Raka Aditya (Sean Institute, 2023)
Promotion Strategy has an important role in agrotourism marketing strategies, being one of the academic studies that has transformed into an interesting and strategic field of study in supporting development, both in terms of the construction of tourist attraction facilities. as well as the development of nurseries in the agro sector . A company uses various forms of marketing communications to promote what they offer and achieve financial goals. The purpose of this research is to explain the promotional strategy carried out by the Taman Bunga Nusantara Company in promoting tourist attractions by offering various types of flowers that exist throughout the world. This research uses qualitative methods that can describe, understand and develop marketing communications for the Taman Bunga Nusantara company obtained from observations and interviews . The theory used is symbolic interactionism. The research results show that implementing a promotional strategy involves promoting a tourist attraction through various methods, from social media, print media, and banners through the marketing concept of advertising, public relations, and personal selling.